2016
DOI: 10.1139/cjps-2014-0440
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan content, viscosity, and solubility of Canadian grown oat as influenced by cultivar and growing location

Abstract: The composition and physicochemical properties of oat flour with respect to β-glucan content and its solubility and viscosity were investigated. Eight oat cultivars grown in 20 prairie locations for three consecutive years were examined in this study to establish how cultivar, growing location, and their interaction influence the abovementioned attributes. It was found that the β-glucan content was primarily influenced by oat cultivar, while growing location and the interaction between cultivar and location ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Also the genetic basis behind the naked trait of oat (A. sativa ssp nudisativa) is being elucidated (Ubert et al, 2017). Herrera et al (2016) tested eight oat varieties on 20 locations in Canada for three years, and determined their composition. They found that the beta-glucan content was primarily influenced by the oat cultivar grown, and hardly by growing location.…”
Section: Breeding Genomics and Cultivation Of Oatmentioning
confidence: 99%
“…Also the genetic basis behind the naked trait of oat (A. sativa ssp nudisativa) is being elucidated (Ubert et al, 2017). Herrera et al (2016) tested eight oat varieties on 20 locations in Canada for three years, and determined their composition. They found that the beta-glucan content was primarily influenced by the oat cultivar grown, and hardly by growing location.…”
Section: Breeding Genomics and Cultivation Of Oatmentioning
confidence: 99%
“…Based on a between-lab SD of mean GI values of 9 (27) the probability that the minimum and maximum values of these ranges come from the same population is small (0•078 for instant oats and 0•030 for rolled oats). Thus, it is likely that the range of GI values for oats reported by Tosh and Chu represents real differences among the oats tested due to factors such as differences in processing (as demonstrated here) or differences in the amounts and physico-chemical properties of the β-glucan they contain due to differences in variety or environmental growing conditions (8,28,29) . If the GI of CR is taken to be 82, the relative glycaemic response for IO could range from 100 × 65/82 = 55 % to 100 × 88/82 = 106 %, a range which overlaps the 95 % CI of the relative glycaemic response for IO we observed (94, 115) (online Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 83%
“…The analysis of variance for the β‐glucan content of the three hulless barley genotypes (Table 1) showed that the effect of the genotype was highly significant at ( P ≤ 0.01) 0.28 ** and 0.33 ** in both seasons, respectively. Many cited researches indicated the significant influence of the genotype on the variations of β‐glucan content (Zhang et al., 2002; Tiwari & Cummins, 2008; Griffey et al., 2010; Dickin et al., 2011; Herrera et al., 2016; Zhang et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The content of β‐glucan in barley is varied from 4% to 12%, 3.9% to 9% in flour, and from 4.9% to 15% in bran. The genotypic, agronomic, and environmental factors had the largest influence in the variation of β‐glucan content (Dickin, Steele, Frost, Edwards‐Jones, & Wright, 2011; Herrera, Gao, Vasanthan, Temelli, & Henderson, 2016; Tiwari & Cummins, 2008; Zhang et al., 2018). Besides, higher yield and concentration of β‐glucan can be achieved by proper extraction conditions using a neutral or an alkaline medium (Burkus & Temelli, 1998; Temelli, 1997; Zhang, Junmei, & Jinxin, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation